How personality moderates the effect of techno-stress on actual use of technology / Nazli Ebrahimi, Rohana Jani and Raida Abu Bakar - Ebrahimi, Nazli; Jani, Rohana; Abu Bakar, Raida (Universiti Teknologi MARA, Shah Alam, 2019)
Implementing new technologies may bring about some positive as well as negative changes.Some negative sideeffects of these changes may cause high turnover or burnout in companies. Meanwhile, as individuals may experience the stress and discomfort of dealing with challenging environment, recruiting process and human resources (HR) managers will be affected as well. Several factors will affect recruiting in various aspects. Among such factors, however, personality of the interviewee is one of the top reasons which could have some sort of significant impact on the rest of criteria. Many studies show the stress that comes from technology, called techno-stress, will affect the perception of users, and several studies demonstrate that the level of techno-stress will vary with personality of the people. However due to lack of studies we need to understand the impact of different aspects of personality on the relationship between techno-stress and adoption of technology. Therefore, this study examined the moderating role of personality on relationship between techno-stress and Technology acceptance and usage. This paper reports on the literature we reviewed to better understand the moderating role of personality on the relationship between techno-stress and perceived ease of use of the technology.